The Influence of Asset Growth And Sales Growth On Profitability In Food And Beverage Companies Listed On The Indonesia Stock Exchange - Anggita Sari Rangkuti; Novien Rialdy (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Problems In this study is the survival of the company is influenced by many things including the profitability of the company itself. Profitability is one of the factors to assess the good or bad performance of the company. The purpose of this study is to determine the effect of asset growth and sales growth on the profitability of food and beverage companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative research method with an associative approach. The sampling method uses the purposive sampling method. The data collection technique used is documentation by means of direct observation and accessing the official website of the Indonesia Stock Exchange. The data analysis technique used is the multiple linear analysis method using SPSS software through the stages of descriptive statistical tests, classical assumption tests and hypothesis tests. The results of this study partially show that asset growth does not affect profitability, this is because it has a negative sign with a t count of -0.943 <t table 1.692, and sales growth does not affect profitability because it has a negative sign t count of -0.588 <t table 1.692 and simultaneously shows that asset growth and sales growth do not affect profitability, this can be seen from f count 1.086 <f table 3.29 in food and beverage companies listed on the Indonesia Stock Exchange so it can be concluded that if asset growth and sales growth increase or decrease, it will not affect profitability in food and beverage companies listed on the Indonesia Stock Exchange